ChemInform Abstract: Establishment of Relative and Absolute Configurations of Phaeosphaeride A: Total Synthesis of ent‐Phaeosphaeride A. Issue 24 (June 2015) - Kobayashi, Kenichi; Kobayashi, Yukiko; Nakamura, Misato; Tamura, Osamu; Kogen, Hiroshi
Abstract: The synthesis of the enantiomer allows the determination of the absolute configuration in the natural product, identified as an anticancer agent.